Florence, Rome, and the origins of the Renaissance - Holmes, George (Clarendon Press, 1986)
The years between 1260 and 1320 saw in Tuscany the flourishing of a rich literary and artistic tradition that signalled the beginning of the Renaissance. This study sets out to place the remarkable cultural achievements of those early years in full historical perspective. Holmes describes the world of Dante and Giotto -- and the circumstances in which their innovations became possible -- through a thorough examination of the politics, economy, culture, and religion of early Renaissance Tuscany, explaining how each of these factors inflenced the art of the period. A comprehensive and abundantly-illustrated historical overview, this book will be welcomed by anyone interested in Renaissance art, literature, or history.